A high BDR microstrip‐line fed antenna with multiple asymmetric elliptical wide‐slots for wideband applications. Issue 7 (28th February 2020) - Kumar, Munish; Nath, Vandana
Abstract: In this study, a novel printed wide‐slot antenna for wideband applications is presented. The designed antenna consists of four merged elliptical wide‐slots (EWSs) of different dimensions in the ground plane. An open‐ended microstrip line having a characteristic impedance of 50 Ω is used to excite the EWS. Each EWS corresponds to the different frequency of operation and hence when merged together give a wideband response. The fabricated prototype of the designed antenna shows the 10 dB return loss bandwidth (RLBW) of about 157.72% ranging from 2.21 to 18.7 GHz. The peak gain varies from 0.1 to 6.5 dB within the RLBW is reported. An almost constant group delay, low variation ( < −40 dB) in the transfer function S 21 and linear phase variation for both side by side and face to face orientations of the designed antenna shows its applicability for wideband applications. The electrical dimensions of about 0.176 λ L × 0.162 λ L (where λ L is the lowest operating wavelength) give rise to the bandwidth dimension ratio of about 5505 which is highest among the antenna structures reported in the literature. The measured results are found in good concordance with the results obtained from numerical simulations.